Pengaruh Variasi Sudut Sudu Turbocyclone terhadap Kinerja Mesin Bensin Satu Silinder - Mohammad Ega Yusriansyah; Yuniarto Agus Winoko (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The purpose of this study is to develop an additional device for vehicles with fuel injection systems to improve fuel consumption efficiency and reduce exhaust emissions, even for older vehicles. The turbocyclone is an auxiliary component installed in the air intake duct before the throttle body to create a swirling airflow entering the combustion chamber. Testing was conducted at engine speeds ranging from 1500 rpm to 6500 rpm, with increments of 1000 rpm. This research aims to minimize fuel consumption and exhaust gas emissions. The experimental method was used, testing exhaust gas contents such as HC, CO, CO₂, and O₂ using a gas analyzer, and measuring fuel consumption based on fuel volume and time. Data processing employed a factorial DOE (Design of Experiments) to analyze results. The dependent variables were exhaust gas emissions and fuel consumption, while the independent variable was the turbocyclone blade angle variations of 20°, 40°, and 60°. The results show that the best reduction in exhaust emissions (HC, CO, CO₂, and O₂) and fuel efficiency occurred at a 40° blade angle, whereas fuel consumption increased at a 60° blade angle.